La Segunda Internacional y el imperialismo Una comparación entre la socialdemocracia alemana y francesa (1896- 1914) - Quiroga, Manuel (Ariadna Ediciones, 2021)
The Second International marked a stage in the history of the labor movement characterized by the formation of mass parties, the growth of trade unions, the development of numerous social organizations and the constitution of an international sphere for the circulation of ideas. In this paper we comparatively investigate the debates on imperialism of two of its most important parties, the German (SPD) and French (SFIO) Social Democracy. We inquire into his analysis of European colonial expansion, the causes of imperialism, and the prospects for a war between the powers. In turn, we examine their political action around these issues and the positions on imperialism of their main internal tendencies, weighing their impact on party politics. Both organizations debated and positioned themselves on these issues within the framework of an agitated political situation marked by wars of conquest, episodes of rebellion in the colonies and various war crises between European states. The contradictory development of these debates is an important factor in explaining the different reactions in these parties to the First World War and the subsequent split of international socialism between communists and reformists.